A Study on the Heterogeneity Characteristics of Geological Controls on Coalbed Methane Accumulation in Gujiao Coalbed Methane Field, Xishan Coalfield, China. (13th March 2021) - Yan, Taotao; He, Shan; Bai, Yadong; He, Zhiyong; Liu, Dameng; Zeng, Fangui; Chen, Xiaozhen; Fu, Xinyu
Abstract : Commercial exploration and exploitation of coalbed methane (CBM) in Gujiao coalbed methane (CBM) field, Xishan coalfield, have rapidly increased in recent decades. The Gujiao CBM field has shown strong gas distribution heterogeneity, low gas content, and wide distribution of wells with low production. To better understand the geological controlling mechanism on gas distribution heterogeneity, the coal reservoir evolution history and CBM accumulation process have been studied on the base of numerical simulation work. The burial history of coal reservoir can be classified into six stages: shallowly buried stage; deeply buried stage; uplifting stage; short-term tectonic subsidence stage; large-scale uplifting stage; and sustaining uplifting and structural inversion stage. Mostly, coal seams have experienced two-time thermal metamorphisms with twice hydrocarbon-generation processes in this area, whereas in the southwest part, the coal seams in there suffered three-time thermal metamorphisms and hydrocarbon-generation processes. The critical tectonic events of the Indosinian, Yanshanian, and Himalayan orogenies affect different stages of the CBM reservoir accumulation evolution process. The Indosinian orogeny mainly controls the primary CBM generation. The Yanshanian orogeny dominates the second and third gas generation and migration processes. The Himalayan orogeny mainly affects the gas dissipation process and current CBM distribution heterogeneity.